EFEK KURKUMIN SINTESIS DAN PENTAGAMAVUNON-0 TERHADAP PRODUKSI PROGESTERON KULTUR SEL LUTEAL DENGAN PEMBERIAN FORSKOLIN - Purwaningsih, Endang; Meiyanto, Edy; Dasuki, Djaswadi; Kadarsih Soejono, Sri (Jurnal Kedokteran YARSI, 2007)
Curcumin is one of the common traditional medicines that is often used for fertility regulation. Curcumin analogue, pentagamavunon-0/PGV-0, exerted similar effect with curcumin. Synthetic curcumin and PGV-0 possesses molecular structures similar to prostaglandin. It has been reported that luteal cells are able to produce progesterone in vitro by addition of several hormones such as LH and prostaglandin F2? (PGF2?). Stimulation of luteal cell cultures with LH and/or PGF2? in the presence of synthetic curcumin and PGV-0 will interfere with the progesterone production. Nevertheless, the precise site of action of curcumin remains unknown. The present study aims to determine the effect of synthetic curcumin and PGV-0 on the progesterone production by luteal cell cultures in the presence or absence of several known stimulators or inhibitors sucs as LH, PGF2? and forskolin, respectively. The results indicated that synthetic curcumin reduced the progesterone concentration significantly (p 0,05) in the luteal cell culture treated with solvent, LH and/or PGF2?, in the presence or absence of forskolin. In the groups treated with PGV-0, and induced with LH and/or PGF2?, the concentration of progesterone did not change significantly (p 0,05). Addition of forskolin on the control group resulted in higher progesterone concentration as that of LH. The findings indicated that synthetic curcumin inhibits progesterone production by the luteal cell cultures through the cAMP/PKA/MAP-Kinase signaling cascade, but PGV-0 might have the site of action in the PLC/PKC/MAP-Kinase signaling cascade.